Changes in local protocols on inpatient cervical priming and introduction of outpatient priming: A nationwide survey in the Netherlands. (August 2021) - Croll, Dorothée M.R.; Hoge, Peter C.; Verhoeven, Corine. J.M.; de Boer, Marjon A.; Bloemenkamp, Kitty W.M.; de Heus, Roel
Abstract: Objective: The aims of this study are to assess (changes in) local procedures for inpatient cervical priming as part of induction of labor and to identify the implementation of outpatient cervical priming in the Netherlands. Methods: This survey study was conducted from October 2019 until January 2020; obstetricians of all 72 hospitals with a maternity unit in the Netherlands received a questionnaire. The questionnaire consisted of three parts: basic hospital data, local protocol on methods of inpatient induction of labor (IPI), local protocol for outpatient induction of labor (OPI). Results: A response was received from 66/72 hospitals, giving a response rate of 92%. For IPI the most preferred method was a Foley catheter (87.9%), 27.6% protocols switched to prostaglandins after day 1 if the cervix was not ripe yet. A prostaglandin gel or pessary was not the preferred method on day 1 but only used after 24 h in 5 hospitals (7.6%). OPI was offered in 53% (35/66 hospitals), all using a Foley catheter. Conclusion: In the Netherlands, local protocols for IPI have shifted towards the use of a Foley catheter. More than half of the hospitals offer OPI. As safety and efficacy data of OPI are lacking, research on this topic is urgently warranted.